IMPLEMENTASI NILAI PANCASILA PADA GENERASI MILENIAL DI ERA SERBA MODERN - Angel Dwi Septianingrum; Dini Anggraeni Dewi (STKIP Al Islam Tunas Bangsa dan HEPI Korda Lampung, 2021)
With the holding of this research, it is in line with the fading of the values ​​of Pancasila implementation in this modern era. It can be seen from some of the behavior of the people who tend to live individually and their focus is only on smart phones whose technology continues to develop. Things like this will certainly throw away the contents of the Pancasila values ​​that have existed for a long time. For this reason, it is necessary to make means or efforts to change this behavior. This research uses a qualitative method, by examining several existing sources such as books, journals or articles. This research is there to obtain an effort or way to realize the implementation of Pancasila in the millennial generation in this modern era. Pancasila is the foundation of the State where we must be guided by all existing values. Key words: Pancasila implementation, Millennial Generation, Pancasila Value